Factors Determining Micro, Small And Medium-Sized Enterprises’ (MSMEs) General Takaful Adoption In Nigeria: The Moderating Role Of Religiosity - Nurudeen Abdulkadir (Universiti Sains Islam Malaysia, 2024)
Matric : 4172003 (FEM)